Intradermal Immunization - Teunissen, Marcel B.M.; Teunissen, Marcel B.M. (Current Topics in Microbiology and Immunology, 2012)
Despite the impressive success of current vaccine programs, there remains a need to improve the effectiveness of current vaccines. A more powerful and longer lasting immune response induced by smaller and fewer doses of vaccine is an exciting challenge. Improvement of effectiveness also enables induction of protective immunity in populations that respond poorly to vaccination, for example elderly or immune-compromised individuals.  This volume of Current Topics in Microbiology and Immunology covers diverse topics related to intradermal immunization. The volume starts with a basic overview of murine and human skin dendritic cell network, respectively, and their role in immunity, as well as an extensive description of the immunobiology of the skin. The next chapter describes the state-of-the-art on delivery systems especially designed for intradermal vaccination. The remaining chapters highlight the effectiveness of intradermal immunization in experimental animal models or in clinical practice, all supporting the view that intradermal immunization is at least as good as other immunization routes. Keeping in mind that current vaccines are not specially designed for intradermal immunization, but show comparable efficiency even at reduced dosages, this underlines the great potential for the skin as a vaccination site Hopefully, the overview in this volume will encourage vaccine designers to focus on this promising immunization route, and in addition, to inspire them to develop vaccines that are especially optimized for intradermal immunization.